1990
DOI: 10.1136/jnnp.53.4.289
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative polymorphism of debrisoquine in Parkinson's disease.

Abstract: Oxidative phenotype and metabolic ratio (MR) of debrisoquine (DBQ) have been determined in 87 patients with Parkinson's disease and in 556 healthy control subjects. Three patients (3-45%) and 34 control subjects (6-12%), having an MR > 12-6, were classified as poor metabolisers (PM) of DBQ (ns).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
2

Year Published

1991
1991
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 29 publications
0
8
2
Order By: Relevance
“…Their MRs varied between 0.22 and 2.40, and the values were not significantly different from MRs of EM parkinsonians with disease onset at the age of over 48 years (range 0.10-5.50). Also, we did not find any reverse correlation between MR and age at disease onset observed in a recent study (24). Therefore, our findings would not support an earlier hypothesis that an environmental neurotoxin (possibly similar to MPTP or MPP + )metabolized by P-450IID6 would cause Parkinson's disease at younger age in PMs, who would be unable to inactivate the compound It has been shown earlier that debrisoquine MR is independent of age or renal clearance of the drug (25)(26).…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Their MRs varied between 0.22 and 2.40, and the values were not significantly different from MRs of EM parkinsonians with disease onset at the age of over 48 years (range 0.10-5.50). Also, we did not find any reverse correlation between MR and age at disease onset observed in a recent study (24). Therefore, our findings would not support an earlier hypothesis that an environmental neurotoxin (possibly similar to MPTP or MPP + )metabolized by P-450IID6 would cause Parkinson's disease at younger age in PMs, who would be unable to inactivate the compound It has been shown earlier that debrisoquine MR is independent of age or renal clearance of the drug (25)(26).…”
Section: Discussioncontrasting
confidence: 68%
“…The results are in accordance with some earlier studies (21)(22). Also, we did not find any reverse correlation between MR and age at disease onset observed in a recent study (24). In our study, all 4 PMs with Parkinson's disease had disease onset at older age than the EMS.…”
Section: Discussioncontrasting
confidence: 63%
“…An initial report by Barbeau et al4" showed a statistically significantly higher number of CYP2D6 PMs in PD patients than in control subjects. This study was flawed because it included PD patients who were taking orphenadrine, which is a substrate of CYP2D6 and thus interferes with the a~s a y .~' Similarly, Benitez et al 42 found a significant correlation between PD and PM phenotypes, but the difference was not statistically significant when the analysis was narrowed to the untreated patients (n = 45). The most comprehensive study was that of Steventon et al,43 who compared drug-naive PD patients with age-matched control subjects and found no difference.…”
Section: Cyp2d6 Pms and Pdmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21][22] Several studies indicate that subjects carrying CYP2D6 alleles containing inactivating mutations are at higher risk for the development of Parkinson's disease. [13][14][15][16][17][18][19][20][21] Although it may be expected that this affects both subjects who are homozygous and subjects who are heterozygous for mutated alleles, most of these studies13*14 '17,18,22 did not find increased frequency of subjects with two defective alleles (poor metabolizers) but did find increased frequency of sub- jects with a single defective allele (intermediate metabolizers). Interestingly, some phenotyping studies indicated a negative correlation between the age of onset of Parkinson's disease and the oxidative capacity, 13,14*17 suggesting that subjects with one CYP2D6 mutant allele are at higher risk for the development of early-onset Parkinson's disease.…”
mentioning
confidence: 99%